Mo-doped boron nitride monolayer as a promising single-atom electrocatalyst for CO2 conversion - Cui, Qianyi; Qin, Gangqiang; Wang, Weihua; Sun, Lixiang; Du, Aijun; Sun, Qiao (Beilstein Journal of Nanotechnology, 2019)
The design of new, efficient catalysts for the conversion of CO2 to useful fuels under mild conditions is urgent in order to reduce greenhouse gas emissions and alleviate the energy crisis. In this work, a series of transition metals (TMs), including Sc to Zn, Mo, Ru, Rh, Pd and Ag, supported on a boron nitride (BN) monolayer with boron vacancies, were investigated as electrocatalysts for the CO2 reduction reaction (CRR) using comprehensive density functional theory (DFT) calculations. The results demonstrate that a single-Mo-atom-doped boron nitride (Mo-doped BN) monolayer possesses excellent performance for converting CO2 to CH4 with a relatively low limiting potential of −0.45 V, which is lower than most catalysts for the selective production of CH4 as found in both theoretical and experimental studies. In addition, the formation of OCHO on the Mo-doped BN monolayer in the early hydrogenation steps is found to be spontaneous, which is distinct from the conventional catalysts. Mo, as a non-noble element, presents excellent catalytic performance with coordination to the BN monolayer, and is thus a promising transition metal for catalyzing CRR. This work not only provides insight into the mechanism of CRR on the single-atom catalyst (Mo-doped BN monolayer) at the atomic level, but also offers guidance in the search for appropriate earth-abundant TMs as electrochemical catalysts for the efficient conversion of CO2 to useful fuels under ambient conditions.
Keywords: boron nitride monolayer; CO2 conversion; density functional theory; single-atom electrocatalyst

(untitled) - Karl, T. R.; Trenberth, K. E. (Science, 2003)

(untitled) - Hoffert, M. I.; Caldeira, K.; Benford, G.; Criswell, D. R.; Green, C.; Herzog, H.; Jain, A. K.; Kheshgi, H. S.; Lackner, K. S.; Lewis, J. S.; Lightfoot, H. D.; Manheimer, W.; et al. (Science, 2002)

(untitled) - D'Alessandro, D. M.; Smit, B.; Long, J. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Pires, J. C. M.; Martins, F. G.; Alvim-Ferraz, M. C. M.; Simoes, M. (Chem. Eng. Res. Des., 2011)

(untitled) - Sun, Q.; Qin, G.; Ma, Y.; Wang, W.; Li, P.; Du, A.; Li, Z. (Nanoscale, 2017)

(untitled) - Whipple, D. T.; Kenis, P. J. A. (J. Phys. Chem. Lett., 2010)

(untitled) - Kondratenko, E. V.; Mul, G.; Baltrusaitis, J.; Larrazábal, G. O.; Pérez-Ramírez, J. (Energy Environ. Sci., 2013)

(untitled) - Liu, C.; Yang, B.; Tyo, E.; Seifert, S.; DeBartolo, J.; von Issendorff, B.; Zapol, P.; Vajda, S.; Curtiss, L. A. (J. Am. Chem. Soc., 2015)

(untitled) - Li, N.; Chen, X.; Ong, W.-J.; MacFarlane, D. R.; Zhao, X.; Cheetham, A. K.; Sun, C. (ACS Nano, 2017)

(untitled) - Kim, S. K.; Zhang, Y.-J.; Bergstrom, H.; Michalsky, R.; Peterson, A. (ACS Catal., 2016)

(untitled) - Hu, G.; Wu, Z.; Dai, S.; Jiang, D.-E. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Costentin, C.; Robert, M.; Savéant, J.-M. (Chem. Soc. Rev., 2013)

(untitled) - Agarwal, A. S.; Zhai, Y.; Hill, D.; Sridhar, N. (ChemSusChem, 2011)

(untitled) - Lu, Q.; Rosen, J.; Zhou, Y.; Hutchings, G. S.; Kimmel, Y. C.; Chen, J. G.; Jiao, F. (Nat. Commun., 2014)

(untitled) - Yan, H.; Cheng, H.; Yi, H.; Lin, Y.; Yao, T.; Wang, C.; Li, J.; Wei, S.; Lu, J. (J. Am. Chem. Soc., 2015)

(untitled) - Xie, L.; Brault, P.; Coutanceau, C.; Bauchire, J.-M.; Caillard, A.; Baranton, S.; Berndt, J.; Neyts, E. C. (Appl. Catal., B, 2015)

(untitled) - Tyo, E. C.; Vajda, S. (Nat. Nanotechnol., 2015)

(untitled) - Kaden, W. E.; Wu, T.; Kunkel, W. A.; Anderson, S. L. (Science, 2009)

(untitled) - Yudanov, I. V.; Genest, A.; Schauermann, S.; Freund, H.-J.; Rösch, N. (Nano Lett., 2012)

(untitled) - Crespo-Quesada, M.; Yarulin, A.; Jin, M.; Xia, Y.; Kiwi-Minsker, L. (J. Am. Chem. Soc., 2011)

(untitled) - Ling, C.; Shi, L.; Ouyang, Y.; Zeng, X. C.; Wang, J. (Nano Lett., 2017)

(untitled) - Qiao, B.; Wang, A.; Yang, X.; Allard, L. F.; Jiang, Z.; Cui, Y.; Liu, J.; Li, J.; Zhang, T. (Nat. Chem., 2011)

(untitled) - Yang, X.-F.; Wang, A.; Qiao, B.; Li, J.; Liu, J.; Zhang, T. (Acc. Chem. Res., 2013)

(untitled) - Zhang, B.; Asakura, H.; Zhang, J.; Zhang, J.; De, S.; Yan, N. (Angew. Chem., Int. Ed., 2016)

(untitled) - Zhang, W.; Zheng, W. (Adv. Funct. Mater., 2016)

(untitled) - Back, S.; Lim, J.; Kim, N.-Y.; Kim, Y.-H.; Jung, Y. (Chem. Sci., 2017)

(untitled) - Liu, S.; Huang, S. (Carbon, 2017)

(untitled) - Zhang, X.; Guo, J.; Guan, P.; Liu, C.; Huang, H.; Xue, F.; Dong, X.; Pennycook, S. J.; Chisholm, M. F. (Nat. Commun., 2013)

(untitled) - Wang, Z.; Zhao, J.; Cai, Q. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Gao, G.; Jiao, Y.; Waclawik, E. R.; Du, A. (J. Am. Chem. Soc., 2016)

(untitled) - He, F.; Li, K.; Yin, C.; Wang, Y.; Tang, H.; Wu, Z. (Carbon, 2017)

(untitled) - Li, X.; Cui, P.; Zhong, W.; Li, J.; Wang, X.; Wang, Z.; Jiang, J. (Chem. Commun., 2016)

(untitled) - Li, X.; Bi, W.; Zhang, L.; Tao, S.; Chu, W.; Zhang, Q.; Luo, Y.; Wu, C.; Xie, Y. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Zhao, J.; Zhao, J.; Li, F.; Chen, Z. (J. Phys. Chem. C, 2018)

(untitled) - Sun, Q.; Li, Z.; Searles, D. J.; Chen, Y.; Lu, G.; Du, A. (J. Am. Chem. Soc., 2013)

(untitled) - Weng, Q.; Wang, X.; Wang, X.; Bando, Y.; Golberg, D. (Chem. Soc. Rev., 2016)

(untitled) - Pang, J.; Chao, Y.; Chang, H.; Li, H.; Xiong, J.; Zhang, Q.; Chen, G.; Qian, J.; Zhu, W.; Li, H. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Watanabe, K.; Taniguchi, T.; Kanda, H. (Nat. Mater., 2004)

(untitled) - Choi, H.; Park, Y. C.; Kim, Y.-H.; Lee, Y. S. (J. Am. Chem. Soc., 2011)

(untitled) - Watanabe, K.; Taniguchi, T.; Niiyama, T.; Miya, K.; Taniguchi, M. (Nat. Photonics, 2009)

(untitled) - Golberg, D.; Bando, Y.; Huang, Y.; Terao, T.; Mitome, M.; Tang, C.; Zhi, C. (ACS Nano, 2010)

(untitled) - Jin, C.; Lin, F.; Suenaga, K.; Iijima, S. (Phys. Rev. Lett., 2009)

(untitled) - Sun, W.; Meng, Y.; Fu, Q.; Wang, F.; Wang, G.; Gao, W.; Huang, X.; Lu, F. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Lin, Y.; Connell, J. W. (Nanoscale, 2012)

(untitled) - Zhao, J.; Chen, Z. (J. Am. Chem. Soc., 2017)

(untitled) - Lin, S.; Ye, X.; Johnson, R. S.; Guo, H. (J. Phys. Chem. C, 2013)

(untitled) - Sun, Q.; Sun, C.; Du, A.; Li, Z. (J. Phys. Chem. C, 2014)

(untitled) - Zhai, L.; Cui, C.; Zhao, Y.; Zhu, X.; Han, J.; Wang, H.; Ge, Q. (J. Phys. Chem. C, 2017)

(untitled) - Azofra, L. M.; MacFarlane, D. R.; Sun, C. (Chem. Commun., 2016)

(untitled) - Wannakao, S.; Artrith, N.; Limtrakul, J.; Kolpak, A. M. (ChemSusChem, 2015)

(untitled) - Backs, S.; Jung, Y. (ACS Energy Lett., 2017)

(untitled) - Li, X.-F.; Li, Q.-K.; Cheng, J.; Liu, L.; Yan, Q.; Wu, Y.; Zhang, X.-H.; Wang, Z.-Y.; Qiu, Q.; Luo, Y. (J. Am. Chem. Soc., 2016)

(untitled) - Le, Y.-Q.; Gu, J.; Tian, W. Q. (Chem. Commun., 2014)

(untitled) - Delley, B. (J. Chem. Phys., 1990)

(untitled) - Delley, B. (J. Chem. Phys., 2000)

(untitled) - Perdew, J. P.; Ernzerhof, M. (J. Chem. Phys., 1996)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Delley, B. (Phys. Rev. B, 2002)

(untitled) - Klamt, A.; Schüürmann, G. (J. Chem. Soc., Perkin Trans. 2, 1993)

(untitled) - Monkhorst, H. J.; Pack, J. D. (Phys. Rev. B, 1976)

(untitled) - Mulliken, R. S. (J. Chem. Phys., 1955)

(untitled) - Zheng, Y.; Jiao, Y.; Zhu, Y.; Li, L. H.; Han, Y.; Chen, Y.; Du, A.; Jaroniec, M.; Qiao, S. Z. (Nat. Commun., 2014)

Computational Chemistry Comparison and Benchmark Database